Case report: A frameshift mutation in CLCN2-related leukoencephalopathy and retinopathy - Cheng, Yizhe; Liu, Xinyu; Sun, Limei; Ding, Xiaoyan (Frontiers in Genetics, 2023)
Background: Leukoencephalopathy and visual impairment have been linked to loss-of-function mutations in the CLCN2 gene (MIM #600570). However, the ocular features caused by the CLCN2 mutations remain poorly understood and seldom reported. This study aims to present a novel mutation and characterize the ocular phenotype in a Chinese female diagnosed with CLCN2-related leukoencephalopathy (CC2L), also known as leukoencephalopathy with ataxia (LKPAT; MIM #615651). Case presentation: A 20-year-old Chinese female presented with bilateral blurred vision persisting for 2 years, which had worsened over the past 6 months. Ophthalmologic examination revealed bilateral post-capsular cataracts, macular retinal atrophy, and peripheral retinal pigmentation. Swept-source optical coherence tomography (SS-OCT) showed bilateral choroidal capillary atrophy, loss of the outer retinal layer, and a novel noteworthy sign of vacuole-like vitreoretinopathy. Cranial magnetic resonance imaging confirmed leukoencephalopathy. Genetic testing identified a novel homozygous pathogenic c.1382_1386del (p.P461Lfs*13) mutation in exon 13 of the CLCN2 gene. Conclusion: This case report expands the knowledge of CLCN2 mutations and their associated ocular manifestations in patients with CC2L. The identified ophthalmic features may serve as crucial indicators for early diagnosis in individuals with CC2L, especially in the absence of evident neurological symptoms.